Enhanced antioxidant phytochemicals and catalase activity of celery by-products by a combined strategy of selenium and PGPB under restricted N supply - Collado-González, Jacinta; Piñero, María Carmen; Otálora, Ginés; López-Marín, Josefa; del Amor, Francisco M. (Frontiers in Plant Science, 2024)
The reduction of N supplied combined with the use of biostimulants can be an efficient strategy that allows sustainable agriculture to achieve better economic, nutritional and environmental goals without reducing production. Moreover, the 2 industrial processing of celery generates large amounts of waste. Therefore the purpose of this study was improve crop management strategies to reduce nitrate pollution while turning crop waste into value-added products for others sectors.Consequently, in this work twelve treatments were examined: three N nitrogen content in the nutrient solution (100% control, 60%, and 30%) combined with the inoculation of the roots with Azotobacter salinestris, and foliar application selenium solution (8 μM, Na2SeO4). The celery parts from plants grown under limited N dose showed a higher antioxidant activity and TPC (total phenolic compounds) content. The antioxidant activity increased 28% in leaves and 41% in by-products and TPC improved 27% in leaves and 191% in by-products respect to the control. Besides, a significant reduction of β-carotene content (56%, 11% and 43% in petioles, leaves and by-products respect to the control, respectively) was obtained in plants fed with restricted dose of N. The catalase activity was not affected by N dose. The inoculation of the plants withAzotobacter, together with a reduced N dose, achieved a greater accumulation of all the parameters studied. This accumulation was maximum when Se was applied to the leaves compared with the control and depending on the celery part: TPC (121-450%); antioxidant activity (60-68%), of catalase activity (59% -158%), and of pigments content (50-90%). These findings can boost the valorization of celery by-products as excellent source of bioactive compounds..